prove that:cosec( a+b)=cosec a cosec b/cot a+cot b
Answers
Answered by
13
Hi ,
1 ) cotA + cot B
= cosA/ sinA + cosB/sinB
= ( SinBcosA + cosBsinA )/(sinAsinB)
= sin( A+ B ) / sinA sinB
= cosecAcosecB/Cosec( A + B )--( 1 )
Now ,
RHS =( cosecAcosecB)/(cotA+cotB)
=(cosecAcosecB)/[(cosecAcosecB)/Cosec(A+B )]
[ From ( 1 ) ]
= Cosec( A+ B )
= LHS
Hence proved.
I hope this helps you.
: )
1 ) cotA + cot B
= cosA/ sinA + cosB/sinB
= ( SinBcosA + cosBsinA )/(sinAsinB)
= sin( A+ B ) / sinA sinB
= cosecAcosecB/Cosec( A + B )--( 1 )
Now ,
RHS =( cosecAcosecB)/(cotA+cotB)
=(cosecAcosecB)/[(cosecAcosecB)/Cosec(A+B )]
[ From ( 1 ) ]
= Cosec( A+ B )
= LHS
Hence proved.
I hope this helps you.
: )
Answered by
1
Step-by-step explanation:
hope it will help you all
Attachments:
![](https://hi-static.z-dn.net/files/d57/c755987c3017b7dab4d7bf92cd59dce5.jpg)
Similar questions